Peran Financial Technology pada UMKM: Peningkatan Literasi Keuangan Berbasis Payment Gateway - Ayu Putu Yulia Kusuma Wardani; Nyoman Ari Surya Darmawan (Universitas Pendidikan Ganesha, 2020)
The purpose of this studi was to understand the financial techology in Micro Small and Medium Entreprises in Buleleng Regency, especially in increased financial literacy based on payment gateway. This research used qualitative approach with the type of descriptive approach and also used primary data and secondary data in the form of interviews observations and documentations. The result showing that the role of financial technology could increase financial literacy and made it easier for Micro Small and Medium Entrepreneurs to manage and understans their finances because the technology provided convenience in digital payments. Therefore, it automatically recorded the income of transsaction that occur.